Career and Family: Women's Century-Long Journey toward Equity - Stevenson, Betsey (Journal of Economic Literature, 2024)
Betsey Stevenson of University of Michigan reviews “Career and Family: Women’s Century-Long Journey toward Equity” by Claudia Golden. The Econlit abstract of this book begins: “Explores the reasons for the persisting gender earnings gap, focusing on women's role in the American economy and how it has transformed over the last century.”